Gender Awareness in Building Self-Efficacy in Student Organization Leadership at School - Hasan Baharun; Moh Tohet (Al-Qalam Institue, 2024)
This research focuses on the forms of gender discrimination that occur in the leadership of student organizations and their impact on female students' self-efficacy. It aims to identify and analyze the various forms of discrimination experienced by female students and their influence on their confidence and participation in organizations. The research method used was a qualitative approach with data collection techniques through in-depth interviews and participatory observation. The results showed that there are four significant forms of gender discrimination: the lack of representation of women in leadership positions, harmful gender stereotypes, the neglect of women's voices in decision-making, and the existence of gender-based violence and bullying. The implications of this study highlight the need for more inclusive policies and support for female students in the school environment to overcome gender discrimination issues and increase their self-efficacy in leadership. This research is expected to be a reference for schools and stakeholders in formulating more effective strategies to create gender equality in student organizations.